A finite element framework for the simulation of bio-inspired adhesives with mushroom-shaped microstructures. (October 2022) - Marulli, M.R.; Heepe, L.; Gorb, S.N.; Paggi, M.
Abstract: This work proposes a finite element procedure for the simulation of biologically inspired adhesives with a mushroom-shaped patterned surface by formulating a novel interface finite element. The proposed computational method can capture the attachment and detachment mechanisms without modeling the microstructures on the surface in detail, which is the major issue of large-scale simulations involving complex surfaces. A data-driven phenomenological interface constitutive law has been formulated starting from pull-out experimental tests on patterned surfaces with different inclination angles to assess Mode Mixity effects in a range of peeling angles of relevance for applications. The proposed computational model represents a versatile tool for modeling structural problems involving arbitrary shape components, as in bio-inspired adhesives.